Análisis de la violencia de género y su impacto en la mujer estudiante de Policía de la Escuela Carlos Eugenio Restrepo (2021)
This article allows the understanding of the phenomenon of genderbased violence as a social problem in Colombia. At the same time, it addresses gender-based violence against female police students at the police school Escuela de Policia Carlos Eugenio Restrepo. It inquired about perceptions, knowledge, positions and types of gender-based violence that, in the students’ opinion, were presented in the description of some facts given in the training process. This allowed the approach with the presence of the phenomenon in the findings obtained, presenting suggestions on institutional policies to deal with it in the police institution. Likewise, it as a work designed to build relationships of equity and respect for the human rights of policewoman.  Finally, it was observed that the students recognized the existence of the phenomenon in the institution, its level of importance, the most representative areas, identification of the main actors, violent demonstrations and actions, acts of discrimination and knowledge of the rules that protect them in the police institution and in society.